Sosialisasi akuntansi syariah idealis bagi mahasiswa akuntansi program diploma - Septyan, Krisno; Maulana, Agus (Pengmasku, 2024)
Diploma Program Accounting students are prepared with various graduate profiles but are not designed as Sharia accountants even though in practice Sharia financial accounting standards have also been issued. Unfortunately, these financial accounting standards have been contaminated by modern accounting science that is godless or secular. So this socialization program needs to be carried out with the aim of liberating the thinking of academic [accountant] communities from the traps of capitalism. The method used is humanist-theocentric in the field of education for both students and the community, socialization is carried out using lecture methods and question and answer discussions. The initial material that we provide is to make students aware that there is a dark side to accounting that needs to be revealed and becomes a reason to migrate towards idealistic accounting. Idealistic Sharia accounting adjusts the form to its place, does not aim to increase assets or make a profit. Idealistic Sharia accounting is often found in everyday life such as household accounting, accounting in the month of Ramadan and hospital accounting. This field needs to be studied by all of us because we will all experience it. Mahasiswa Akuntansi Program diploma dipersiapkan dengan berbagai profil lulusan tapi tidak dirancang sebagai akuntan Syariah padahal prakteknya juga telah terbit standar akuntansi keuangan Syariah. Sayangnya standar akuntansi keuangan tersebut telah terkontaminasi sains akuntansi modern yang tidak berketuhanan atau bersifat sekular. Sehingga program sosialisasi ini perlu dilakukan dengan tujuan untuk membebaskan pemikiran sivitas [akuntan] akademisi dari jerat-jerat kapitalis. Metode yang digunakan adalah humanis-teosentris dalam bidang pendidikan baik kepada mahasiswa maupun masyarakat, sosialisasi dilakukan dengan metode ceramah dan diskusi tanya jawab. Materi awal yang kami berikan adalah menyadarkan kepada mahasiswa bahwa ada sisi gelap akuntansi yang perlu diungkap dan menjadi alasan untuk hijrah menuju akuntansi idealis. Akuntansi Syariah idealis menyesuaikan bentuk pada tempatnya, tidak bertujuan untuk meningkatkan asset ataupun memperoleh laba. Akuntansi syariah idealis banyak ditemui dalam kehidupan sehari-hari seperti akuntansi rumah tangga, akuntansi di bulan ramadhan dan akuntansi rumah sakit. Bidang tersebut perlu dipelajari oleh kita semua karena kita semua akan mengalaminya.